Analisis Profitabilitas Perbankan Syariah Terdaftar Pada Bursa Efek Indonesia Pada Periode 2020-2021 - Nurmitananda, Muhammad Naufal Hamdani; Santoso, Ridho Bagus; Primasatya, Rieswandha Dio (Politeknik Ganesha Medan, 2024)
Management company performance can be assessed by analyzing the financial statements of a company. To be able to find out the company's financial condition, various analyses can be carried out, one of which is ratio analysis. The purpose of this study was to determine the financial performance of Islamic banking companies listed on the Indonesia Stock Exchange in terms of financial ratio analysis. The analytical method used is descriptive quantitative analysis with the measurement of profitability ratios. The research data is secondary data in the form of annual reports for each bank obtained from the official website of the Indonesia Stock Exchange or the official website of each Islamic bank. The results of the study show that several ratios used to measure the profitability aspects of Islamic banking, namely the ROA, ROE, NIM, and BOPO ratios, decreased significantly in 2021 when compared to 2020